2021
DOI: 10.1177/2320206821998569
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Perspectives of Orthodontists and Laypersons About the Effect of Orthodontic Treatment on Facial Aesthetics of Young Turkish Patients

Abstract: Aim: To compare the perspective of orthodontists and laypersons on the effects of orthodontic treatment on facial aesthetics in young Classes I, II, and III Turkish patients. Materials and Methods: In this cross-sectional study, a total of 60 patients (30 males and 30 females, 9 to 17 years of age) was included using randomization in strata and then divided equally ( n = 15) into four groups according to the Angle classification. Photographs during frontal and lateral resting and also smiling were obtained fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…Achieving aesthetic results in these cases is difficult because the camouflage corrects the dental occlusion with little influence on facial characteristics [22]. Many previous studies have shown that some orthodontic treatments do not necessarily change aesthetic outcomes [16,[26][27][28], and having ideal measurements is not essential for facial attractiveness [29,30]. Thus, for the best aesthetic results, it is fundamental to know the unpleasant facial characteristics that should be improved with orthodontic treatment and the nice features that should be achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving aesthetic results in these cases is difficult because the camouflage corrects the dental occlusion with little influence on facial characteristics [22]. Many previous studies have shown that some orthodontic treatments do not necessarily change aesthetic outcomes [16,[26][27][28], and having ideal measurements is not essential for facial attractiveness [29,30]. Thus, for the best aesthetic results, it is fundamental to know the unpleasant facial characteristics that should be improved with orthodontic treatment and the nice features that should be achieved.…”
Section: Introductionmentioning
confidence: 99%